Aiding and Abetting: The Responsibility of Business Leaders under the Rome Statute of the International Criminal Court. Issue 79 (19th August 2014) - Plomp, Caspar
While no business leaders have yet been charged before the International Criminal Court (ICC), such future proceedings will typically be conducted with reference to the accessorial mode of liability of aiding and abetting, under Article 25(3)(c) of the Rome Statute of the ICC. There exist diverse and competing interpretations of Article 25(3)(c). This paper aims to advocate the creation of a dominant interpretation of Article 25(3)(c) and, consequently, to the clarification of the potential responsibility of business leaders who aid or abet crimes under the jurisdiction of the Rome Statute, in two ways. First, it asks whether Article 25(3)(c) can be interpreted in harmony with the dominant practice on aiding and abetting in international criminal law generally. Second, it presents a case study on the provision of arms by the Russian corporation Rosoboronexport to the Syrian government, which is likely to have committed crimes against humanity since March 2011 and war crimes since mid-2012. The theoretical conclusions are applied to a discussion on the potential criminal responsibility of the Director General of Rosoboronexport for aiding and abetting the commission of international crimes by high-level Syrian officials.